Folate receptor-targeted positron emission tomography of experimental autoimmune encephalomyelitis in rats - Elo, Petri (J Neuroinflammation, 2019)
BACKGROUND: Folate receptor-β (FR-β) is a cell surface receptor that is significantly upregulated on activated macrophages during inflammation and provides a potential target for folate-based therapeutic and diagnostic agents. FR-β expression in central nervous system inflammation remains relatively unexplored. Therefore, we used focally induced acute and chronic phases of experimental autoimmune encephalomyelitis (EAE) to study patterns of FR-β expression and evaluated its potential as an in vivo imaging target. METHODS: Focal EAE was induced in rats using heat-killed Bacillus Calmette-Guérin followed by activation with complete Freund’s adjuvant supplemented with Mycobacterium tuberculosis. The rats were assessed with magnetic resonance imaging and positron emission tomography/computed tomography (PET/CT) at acute (14 days) and chronic (90 days) phases of inflammation. The animals were finally sacrificed for ex vivo autoradiography of their brains. PET studies were performed using FR-β-targeting aluminum [(18)F]fluoride-labeled 1,4,7-triazacyclononane-1,4,7-triacetic acid conjugated folate ([(18)F]AlF-NOTA-folate, (18)F-FOL) and 18 kDa translocator protein (TSPO)-targeting N-acetyl-N-(2-[(11)C]methoxybenzyl)-2-phenoxy-5-pyridinamine ((11)C-PBR28). Post-mortem immunohistochemistry was performed using anti-FR-β, anti-cluster of differentiation 68 (anti-CD68), anti-inducible nitric oxide synthase (anti-iNOS), and anti-mannose receptor C-type 1 (anti-MRC-1) antibodies. The specificity of (18)F-FOL binding was verified using in vitro brain sections with folate glucosamine used as a blocking agent. RESULTS: Immunohistochemical evaluation of focal EAE lesions demonstrated anti-FR-β positive cells at the lesion border in both acute and chronic phases of inflammation. We found that anti-FR-β correlated with anti-CD68 and anti-MRC-1 immunohistochemistry; for MRC-1, the correlation was most prominent in the chronic phase of inflammation. Both (18)F-FOL and (11)C-PBR28 radiotracers bound to the EAE lesions. Autoradiography studies verified that this binding took place in areas of anti-FR-β positivity. A blocking assay using folate glucosamine further verified the tracer’s specificity. In the chronic phase of EAE, the lesion-to-background ratio of (18)F-FOL was significantly higher than that of (11)C-PBR28 (P = 0.016). CONCLUSION: Our EAE results imply that FR-β may be a useful target for in vivo imaging of multiple sclerosis-related immunopathology. FR-β-targeted PET imaging with (18)F-FOL may facilitate the monitoring of lesion development and complement the information obtained from TSPO imaging by bringing more specificity to the PET imaging armamentarium for neuroinflammation.